Respuesta :
y^2 + 7 = 6y
First step: shift everything to one side
y^2 + 7 - 6y = 0
Second step: rearrange terms to fit the formula ax^2 + bx + c
y^2 - 6y + 7 = 0
Note in this equation a = 1, b = -6 and c = 7
Quadratic formula in general is x = (-b +/- Squareroot (b^2 - 4ac)) / 2a
so in this case it’ll be something like y= (-(6) +/- squareroot of ((-6)^2 - 4 (1)(7))/ 2(1)
You should key it into a calculator and get y = 4.41 and y = 1.59 (both rounded to 3 significant figures)
First step: shift everything to one side
y^2 + 7 - 6y = 0
Second step: rearrange terms to fit the formula ax^2 + bx + c
y^2 - 6y + 7 = 0
Note in this equation a = 1, b = -6 and c = 7
Quadratic formula in general is x = (-b +/- Squareroot (b^2 - 4ac)) / 2a
so in this case it’ll be something like y= (-(6) +/- squareroot of ((-6)^2 - 4 (1)(7))/ 2(1)
You should key it into a calculator and get y = 4.41 and y = 1.59 (both rounded to 3 significant figures)